Experimental results from the ST7 mission on LISA Pathfinder - Anderson,G; Anderson,J; Anderson,M; Aveni,G; Bame,D; Barela,P; Blackman,K; Carmain,A; Chen,L; Cherng,M; Clark,S; Connally,M; et al. (Physical Review D, 2018)
The Space Technology 7 Disturbance Reduction System (ST7-DRS) is a NASA technology demonstration payload that operated from January 2016 through July 2017 on the European Space Agency’s (ESA) LISA Pathfinder spacecraft. The joint goal of the NASA and ESA missions was to validate key technologies for a future space-based gravitational wave observatory targeting the source-rich millihertz band. The two primary components of ST7-DRS are a micropropulsion system based on colloidal micro-Newton thrusters (CMNTs) and a control system that simultaneously controls the attitude and position of the spacecraft and the two free-flying test masses (TMs). This paper presents our main experimental results and summarizes the overall performance of the CMNTs and control laws. We find the CMNT performance to be consistent with preflight predictions, with a measured system thrust noise on the order of 100  nN/√Hz in the 1  mHz≤f≤30  mHz band. The control system maintained the TM-spacecraft separation with an RMS error of less than 2 nm and a noise spectral density of less than 3  nm/√Hz in the same band. Thruster calibration measurements yield thrust values consistent with the performance model and ground-based thrust-stand measurements, to within a few percent. We also report a differential acceleration noise between the two test masses with a spectral density of roughly 3  fm/s2/√Hz in the 1  mHz≤f≤30  mHz band, slightly less than twice as large as the best performance reported with the baseline LISA Pathfinder configuration and below the current requirements for the Laser Interferometer Space Antenna mission.